Mesostructural Evolution of Iron Oxide-SDS Composites: A TEM and PXRD Study - Li, Feihu; Nie, Dongyang (Asian Journal of Chemistry, 2014)
In present study, we synthesized iron oxide-sodium dodecyl sulfonate (SDS) composites by using a solvothermal route (ethyl alcohol-water) and demonstrated that the iron oxide-SDS composites undergo a mesostructural transition from lamellar to hexagonal as a function of ageing time. With increasing ageing time, the composite mesostructure evolved from a regular lamellar symmetry to a transitional lamellar-hexagonal symmetry and eventually to an ordered hexagonal symmetry with a unit cell parameter of a = 44 Å. The direct evidences of mesostructural evolution were acquired from transmission electron microscopy and further confirmed by powder X-ray diffraction. A lamellar-to hexagonal transition mechanism was proposed to explain the mesostructural transition of iron oxide-SDS composites.